Perilaku Hidup Bersih dan Sehat (PHBS) Nelayan Tradisional saat di Kapal - Fadlilah, Nazilatul; Halim, Arif Rahman (Universitas Negeri Semarang, 2023)
The traditional fishermen spent more time at sea than land, thus requiring fishermen to lived on boats for many days. Therefore, it is necessary to study the clean and healthy behavior (PHBS) of traditional fishermen while at workplace, namely boats. This article used quantitative method with cross sectional design. A description of fishermen's PHBS was obtained by using interviews and observation of 15 fishermen. PHBS assessment of fishermen refers to Regulation of Kementerian Kesehatan Republic Indonesia 2269/MENKES/PER/XI/2011, about guidelines PHBS in workplace. It was founded that were PHBS practices in the workplace not carried out by traditional fishermen, that were using healthy toilets, smoking in the workplace, and eradicating mosquito larvae. The results of chi-square analysis between fishermen's characteristics for PHBS practices, it was founded that there was no effect of characteristics (age, status and boat ownership, education, and income) to PHBS practices of fishermen in Dungkek District (p=0,426, p=0,476, p=0,560, p=0,930)